TATHWIZR NAMIDZAJ AL-MUQARRAR AL-DIRASIZ LI MADAH TASHMIZM TADRIZS AL-LUGHAH AL-‘ARABIYYAH ‘ALA ASAS AL-NASYATHAT - Raswan, Raswan (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
This research was aimed to develop syllabus of Arabic Learning Planning course. The syllabus to be developed is a syllabus that enables the students to develop good planning in learning Arabic language based on both the theory of unity (All in One System / Ù†Ø¸Ø±ÙŠØ© Ø§Ù„ÙˆØØ¯Ø©) and branch theory (Ù†Ø¸Ø±ÙŠØ© Ø§Ù„ÙØ±ÙˆØ¹). The design of learning is essentially a skill; therefore the learning should be activity-based. If not, the students who study development will not be proficient. This paper discussed a syllabus model that is able to develop Arabic learning designs for madrasah, schools and pesantren in which Arabic language is taught and activity-based.